Zr doping effect with low-cost solid-state reaction method to synthesize submicron Li4Ti5O12 anode material. (September 2017) - Seo, Inseok; Lee, Cheul-Ro; Kim, Jae-Kwang
Abstract: To improve the electrochemical properties, fine Zr-doping Li4 Ti5 O12 anode materials for rechargeable lithium batteries with a uniform particle size distribution were synthesized by a modified solid-state reaction using fine Li2 CO3 and TiO2 (anatase) powders as precursors with a Li:Ti molar ratio of 4:5. The use of fine Li2 CO3 and TiO2 (anatase) powders as precursors prevented the formation of ZrO2 at 0.1 mol Zr-doping. XRD analysis revealed that the substitution of Zr for Ti leads to the increase of lattice parameters, allowing improved Li diffusion. The discharge capacity retention increased slightly with Zr-doping and the 0.1 mol Zr-doped Li4 Ti5 O12 electrode achieved 99% retention of discharge capacity. Graphical abstract: Highlights: Fine Zr-doped Li4 Ti5 O12 powders were prepared by a modified solid-state reaction. High electrochemical properties were achieved with the increase in Zr-doping. 0.1 mol Zr-doped Li4 Ti5 O12 electrode achieved 99% retention of discharge capacity.